The Work of Mourning Death in a Punjabi Family - Das, Veena; Harvard Univ., Cambridge, MA. Graduate School of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
One particular death and the rituals, funeral ceremony, and mourning which followed it are used to explore the relationship of the living to death. The particular death described was one which occurred during a year of fieldwork among urban Punjabis. By examining the category of mourners, it was possible to discern a structure within which grief and loss were articulated and thus the connections between individual grief and societal patterns of mourning were made apparent. Life and death are seen as polar opposites between which rituals of mourning must mediate. This mediation becomes possible only if we conceptualize the mourners in this culture as a heterogeneous group rather than a homogeneous one. The heterogeneity is provided by the sharp distinction in the roles of women and men on the one hand and kin and affines on the other. It is their differential symbolic function that allows the work of mourning to proceed by making it possible for mediation between life and death to occur. Suggestions are also made for extending this perspective to cross-cultural situations. (IS)
Sponsoring Agency: Bernard Van Leer Foundation, The Hague (Netherlands).
ERIC Note: Paper from the Project on Human Potential. For other project papers, see SO 016 244-270.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Anthropology; Case Studies; Death; Ethnography; Ethnology; Family Structure; Foreign Countries; Grief; Religion; Sex Role; Social Theories; Sociocultural Patterns; Widowed; Panjabi; Reports, General